Salmonella Interacts With Autophagy to Offense or Defense - Wu, Shu; Shen, Yiru; Zhang, Shan; Xiao, Yunqi; Shi, Shourong (Frontiers in Microbiology, 2020)
Autophagy is an important component of the innate immune system in mammals. Low levels of basic autophagy are sustained in normal cells, to help with the clearance of aging organelles and misfolded proteins, thus maintaining their structural and functional stability. However, when cells are faced with challenges, such as starvation or pathogenic infection, their level of autophagy increases significantly. Salmonella is a facultative intracellular pathogen, which imposes an economic burden on the poultry farming industry and human public health. Previous studies have shown that Salmonella can induce the autophagy of cells following invasion, which to a certain extent helps to protect the cells from bacterial colonization. This review summarizes the latest research in the field of Salmonella-induced autophagy, including: i) the autophagy induction and escape mechanisms employed by Salmonella during the infection of host cells; ii) the effect of autophagy on intracellular Salmonella; iii) the important autophagy adaptors that recognize intracellular Salmonella in host cells; and iv) the effect of autophagy-modulating drugs on Salmonella infection.